An Unusual Presentation of Corneal Intraepithelial Neoplasia: A Case Report - Bajracharya, Leena; Sapkota, Jyoti (Nepalese Journal of Ophthalmology, 2022)
Introduction: Corneal squamous neoplasia is less common than that of conjunctiva and can cause diagnostic confusion. Case: A 40-year-old male presented with gradual onset blurring of vision in left eye for 8 weeks. He had received treatment for dry eyes, then for herpetic dendritic keratitis, but without improvement. On slit-lamp examination with diffuse light, apparently the cornea looked clear with some dilated conjunctival vessels nasally. But in the retro-illumination, on the corneal surface, there was a translucent inverted “V” shaped lesion with irregular fimbricated margin. He underwent excisional biopsy of the corneal lesion and the adjacent conjunctiva. Cryotherapy of the conjunctival margin and the adjoining limbus was done. Corneal and conjunctival specimens reported intraepithelial neoplasia grade II and I respectively.There had not been any recurrence till 4 year post-operatively. Conclusion: Corneal examination by retro-illumination aids to diagnose and demarcate corneal intraepithelial neoplasia clinically. Timely management results in good prognosis.